2005
DOI: 10.1152/ajpcell.00023.2005
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia and acidosis increase the secretion of catecholamines in the neonatal rat adrenal medulla: an in vitro study

Abstract: Hypoxia elicits catecholamine (CA) secretion from the adrenal medulla (AM) in perinatal animals by acting directly on chromaffin cells. However, whether innervation of the AM, which in the rat occurs in the second postnatal week, suppresses this direct hypoxic response is the subject of debate. Opioid peptides have been proposed as mediators of this suppression. To resolve these controversies, we have compared CA-secretory responses with high external concentrations of K+ ([K+]e) and hypoxia in the AM of neona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
37
0
7

Year Published

2006
2006
2019
2019

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(46 citation statements)
references
References 44 publications
2
37
0
7
Order By: Relevance
“…We showed that at birth, the release of adrenaline was defective in FR50 pups, suggesting that FR50 newborns were likely less sensitive to the stress associated with birth. In addition, it suggests that maternal FR50 impaired the non-neurogenic control of catecholamine release because at this stage, splanchnic control of the adrenal medulla is not yet effective [39,40,41,42]. This is in accordance with the observation that intrauterine growth retardation led to the complete loss of adrenaline synthesis and release in response to hypoxia [43, 44].…”
Section: Discussionsupporting
confidence: 62%
“…We showed that at birth, the release of adrenaline was defective in FR50 pups, suggesting that FR50 newborns were likely less sensitive to the stress associated with birth. In addition, it suggests that maternal FR50 impaired the non-neurogenic control of catecholamine release because at this stage, splanchnic control of the adrenal medulla is not yet effective [39,40,41,42]. This is in accordance with the observation that intrauterine growth retardation led to the complete loss of adrenaline synthesis and release in response to hypoxia [43, 44].…”
Section: Discussionsupporting
confidence: 62%
“…2Ai,Bi. Acute hypoxia also induces CAT secretion when applied to fresh tissue slices of the adrenal gland (García-Fernández et al, 2007), and to superfused whole adrenal glands (Adams et al, 1996;Rico et al, 2005) In nicotine-treated AMCs, hypoxia does not affect outward K + current, although hypercapnia still produces significant inhibition at +30 mV. In current-clamp recordings, both hypoxia (Bi) and isohydric hypercapnia (10% CO 2 , pH 7.4; Ci) produce depolarizing excitatory responses in salinetreated AMCs.…”
Section: Mechanisms Of Acute Hypoxia Sensing In Perinatal Amcsmentioning
confidence: 99%
“…Furthermore, they showed in denervation experiments that removal of the splanchnic innervation in mature or adult animals resulted in a gradual re-appearance of this non-neurogenic mechanism (Slotkin and Seidler, 1988). More recent studies in the rat suggest that adrenal responses to hypercapnia, acidity and hypoglycemia are also suppressed postnatally, in parallel with splanchnic innervation (Livermore et al, 2011;Livermore et al, 2012;Muñoz-Cabello et al, 2005;Rico et al, 2005). Interestingly, in mammals that are born relatively mature (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…We can name these cells as cells endowed with sensitivity to physiological hypoxia (Gonzalez, 1998). Neonatal adrenal medulla chromaffin cells are also endowed with sensitivity to physiological hypoxia, however they lose their intrinsic O 2 -sensitivity early in postnatal age when adrenal medulla becomes functionally innervated by splanchnic nerves (Seidler and Slotkin, 1985;Rico et al, 2005). Chemoreceptor cells of the airways neuroepithelial bodies also are oxygen sensitive in neonatal animals (Cutz et al, 2009), but become greatly atrophic in adult mammals (Cutz, 1997).…”
Section: The Need For Oxygen Sensing and Transduction Cascadesmentioning
confidence: 99%